STRATEGI PENINGKTAN PASRTISPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KABUPATEN ACEH BARAT - Mardhatillah, Muntaha; Kahanna, Mutia; Pratama, Agus (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2025)
Waste management is one of the main challenges in West Aceh District, along with the increase in population and waste volume. Low community participation in waste management is a major cause of environmental problems, such as pollution and the emergence of various diseases. This study aims to analyze effective strategies in increasing community participation in waste management in the region. The research method used is descriptive qualitative method with data collection techniques through interviews, observations, and documentation studies. The results show that the main factors influencing community participation are lack of awareness, education, and supporting facilities. In addition, the policy implementation of Qanun No. 4/2017 on Waste Management has not run optimally, especially in terms of socialization and law enforcement. The proposed strategy includes increasing socialization and education on the importance of waste management, developing community-based programs such as Waste Bank, providing adequate infrastructure, and collaboration between the government, community, and private sector. With these strategies, it is expected that the level of community participation in waste management can increase significantly, thus creating a cleaner and healthier environment.